Ureteric Laser Tripsy with and without Stone Cone: Ureteric Laser Tripsy - Khan, Muhammad Salman; Farooq, Khalid (Pakistan Journal of Health Sciences, 2023)
Stones may block the ureter causing pain and discomfort. Ureteric laser lithotripsy, a notable breakthrough in urology, has transformed the treatment of urinary tract stones. Objectives: To compare the efficacy of ureteroscopic laser lithotripsy with and without stone cone. Methods: This retrospective analysis was done at LRH Peshawar’s urology department from 1st December 2022 to 31th October 2023. Over the time, 50 patients had ureteroscopic holmium laser lithotripsy. Our research comprised adults over 18 with proximal ureteric stones (>10mm) and hydro ureters on CT KUB. Patients were split into two groups. Group A included 27 patients and employed a 7mm stone cone (Boston Scientific Corp, Natick, MA). No stone cone was utilized in group B (23). Results: This prospective research included 50 adults with radiologically confirmed uretric stones in diverse ureteric sites. Male 35 (70%) and female 15 (30%) were 21–68 years old (mean 38.6 years). Stones size varied from 6 to 20 mm, averaging 12.6mm. Proximal stones were 8–20mm (mean 13.9). Mid-ureter stones were 7–18mm (mean 12.6). Lower ureter stones ranged from 6 to 16mm, with a mean of 11.9mm. Ten (20%) patients have normal pelvicalyceal systems. Patients with moderate hydronephrosis were 27 (55%). Conclusions: The use of a stone cone during ureteroscopic lithotripsy is a safe and effective technique for the management of ureteric stones.